Hungarian Monitoring, 11 March 1989 . [Magyar rádiófigyelő], 1989. március 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - CPSU Central Committee plenum begins - Sajudis leader voted in as chair of the Lithuanian parliament - Telephone interview with co-president of Ukrainian People's Movement RUKH - Brandt's visit to the Polish-German border - Catholic church wants greater role in Polish public life - Regeneration of the Italian CP Domestic Affairs: - Soviet troop withdrawals - Exclusive interview with Otto Habsburg - Situation of the Hungarian national minority in Romania - Elections: election announcements, rallies, technical arrangements Economy: - Economics Society's analysis of the crisis - Brzezinski interview - Mining in financial crisis - Suzuki firm Külpolitika: - Megkezdődött az SZKP-KB plénuma - A Szajudisz vezetőjét választották a litván parlament elnökévé - Telefoninterjú az ukrán RUH társelnökével - Brandt látogatást tett a lengyel-német határnál - A katolikus egyház kevesli szerepét a lengyel közéletben - Az Olasz KP megújhodásáról Belpolitika: - Szovjet csapatkivonás - Exkluzív interjú Habsburg Ottóval - Romániai magyar nemzetiség helyzete - Választás: választási hirdetések, műsorok,nagygyűlések, technikai lebonyolítás Gazdaság: - A Közgazdasági Társaság válságelemzése - Brzezinski interjú - Pénzügyi válságban a bányászat - Suzuki cég